The Correlation Between English Language Education Students’ Speaking Anxiety and Their Speaking Fluency - Ayuni, Ni Luh Chandra; Sulistia Dewi, Ni Luh Putu Eka; Paramartha, A.A Gede Yudha (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the correlation between English Language Education (ELE) students’ speaking anxiety and their speaking fluency. This is a quantitative research which consists of 95 students from the 2nd semester as the sample. The data of students’ speaking anxiety were collected through questionnaire namely FLCAS (Foreign Language Anxiety) which was adopted from Horwitz and Cope. While the data of speaking fluency were collected by using speaking test. There are two variables in this research, students’ speaking anxiety as the independent variable and students’ speaking fluency as the dependent variable. The data were analyzed by using SPSS and Pearson Product Moment was used to find out the relationship between the two variables. The result showed that there was a significant and negative correlation between students’ speaking anxiety and their speaking fluency. The significant value is .045<.05 and the value of correlation is -206. The negative correlation in this research indicates that there is an inverse correlation between those two variables. The students obtain low level of anxiety and achieved a high-level score in speaking fluency.